“Light in and Sound Out”: Review of Photoacoustic Imaging in Cardiovascular Medicine - Da-Ya Yang; Yuan Zhu; Jian-Qiu Kong; Xiao-Jing Gong; Zhi-Hua Xie; Wei-Yi Mei; Chu-Fan Luo; Zhi-Min Du; Xiao-Dong Zhuang; Xin-Xue Liao (IEEE Access, 2019)
Photoacoustic imaging (PAI) is one of the most recent additions to the expanding armamentarium of diagnostic imaging technologies. Based on the working principles of optics and ultrasound, PAI provides relatively accurate, differential, and comprehensive information for a variety of physiological and pathological conditions in a real-time fashion. PAI was previously put to use in the field clinical oncology and has only recently been attempted in diseases of the heart and vessels. Notwithstanding the fact that it is still in the pre-clinical stage, PAI, with its important advances, has shown considerable potential to make a significant, transformative leap forward in cardiovascular imaging. The applications of PAI-based techniques in cardiovascular medicine include, but are not limited to, the identification and evaluation of atherosclerotic vulnerable plaque (with or without the use of tissue-specific extraneous contrast), the visualization of clots in different thrombosis-related diseases, the detection of myocardial lesions during catheter ablation of cardiac arrhythmias, the real-time monitoring of blood rheology and hemodynamics, and so on. In this contemporary literature review, we have summarized major applications of different PAI-based techniques for various cardiovascular situations, highlighted key innovations, and their respective clinical feasibilities, and then discussed future perspectives of these versatile methodologies in the practice of cardiovascular imaging. In our view, the unique advantages of PAI render it immensely promising to open up new avenues in the study of cardiovascular diseases.